Homework in Primary Education from the Perspective of Teachers and Pupils. (5th February 2016) - Costa, Marina; Cardoso, Ana Paula; Lacerda, Carla; Lopes, Ana; Gomes, Celeste
Abstract: This study aims to understand the perceptions of teachers and students of the 4 th year of schooling regarding homework and its relationship with the act of studying. A comparative research of a descriptive-correlational nature was undertaken, comprising two questionnaires one to the teachers and another to their pupils. The study covered a sample of fourteen primary teachers from all Nelas municipality state schools (central region of Portugal), and 128 pupils, aged from 9 to 11 years and of both sexes, in identical percentage. Data obtained show that all teachers ask their students to do homework, especially in the areas of Portuguese and Mathematics and consider it essential for learning. The students generally like to do their homework and consider it important. For the most part, if they could decide, students would do homework because it helps them to consolidate the content taught. Knowing the teachers and students perceptions about the homework is fundamental to developing teaching strategies that contribute to the academic success of all students.